2016
DOI: 10.1515/openec-2018-0006
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Migration to Economics Growth. Evidence from Spain

Abstract: Productivity is crucial for economic growth. In a time of challenges such as the population ageing, a growing migration flows and slowdown of the economy it is very important to know the impact of migrant workers in productivity and development. Therefore, this paper studies relevant migration theories and the evolution of migration flows, productivity and their effect on economic growth. We analyse the contribution of immigrants’ workers to productivity, to the employment rate and to the demography of Spain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In origin countries, the benefits of migration comprise reduced unemployment and social spending, incomes from remittances and foreign direct investment. And as for receiving countries, foreign workers contribute to higher participation rates, an increased number of young workers, new income through taxes and social contributions (Mihi-Ramirez et al, 2018;Grossman & Stadelmann, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In origin countries, the benefits of migration comprise reduced unemployment and social spending, incomes from remittances and foreign direct investment. And as for receiving countries, foreign workers contribute to higher participation rates, an increased number of young workers, new income through taxes and social contributions (Mihi-Ramirez et al, 2018;Grossman & Stadelmann, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Productivity is crucial for the level of development (OECD, 2019a;Mihi-Ramirez et al, 2018), but its global growth has remained very limited. In fact, productivity growth for the Eurozone has declined from 2 % in the 1990s to less than 0.5 % today, and this is also the case in the United States and other developed economies (OECD, 2019a;Gordon, 2016;European Commission, 2014;Ark et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The findings show that migration leads to a slight increase in wages for high-and medium-skilled workers with the highest immigration rates. Examining the contribution of migration to growth for Spain, Mihi-Ramírez et al (2016) found that the impact of migration on development level was small but positive. Bove and Elia (2017), It has been determined that immigrants living outside their countries of origin generally have a positive impact on real GDP per capita and that the impact of diversity is more consistent in developing countries.…”
Section: Li̇teraturementioning
confidence: 99%